Femoral Neck Fracture Treated with Dynamic Hip Screw System with De-rotation Screw Versus Cannulated Hip Screws - Saha, Shantonu Kumar; Hira, Hasina Momotaj; Jahangir, Jabed; Deb, Ajoy; Mustafa, Mamun; Ghosh, S Ripon Kumar (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Fracture neck of femur has always presented a great challenge to orthopedic surgeons due to its nature of going into non-union and osteonecrosis of femoral head even with the best fixation method and adequate reduction. Treatment of fracture neck of femur varies according to patient’s age and fracture pattern. Purpose of this study was to compare the outcome of DHS with side plate and de-rotation screw with multiple cannulated hip screws in fracture neck of femur in adult. Materials and methods: This quasi-experimental study was carried out in the Department of Orthopedic Surgery, Chittagong Medical College Hospital from July 2017 to June 2019. Sixty patients age limit between 18 to 55 years, with (AO/OTA 31-B) fracture was taken by purposive sampling technique as per set criteria and were treated either by DHS with side plate and de-rotation screw or by cannulated hip screws. Harris Hip Score was used for evaluation of functional outcome of surgery. Results: In this study, out of 60 patients, male (83%) were more than female (17%), maximum age incidence was found in 26-36 years age group (30%), left side involvement was 51.7% and right side was 48.3%. Over 60% incidence was due to RTA. Functional outcome was 68% excellent and 24% good in DHS with de-rotation screw group and 55.6% good and 25.9% excellent in cannulated hip screw group according to Harris Hip Score. Only 6.7% had soft tissue infection, 13.3% had deep seated infection and delayed union, 10% had non-union and hip stiffness and 6.7% had AVN in DHS with de- rotation screw group and 10% had soft tissue infection, 6.7% had deep seated infection and delayed union, 13.33% had non-union and hip stiffness and 10% had AVN in cannulated hip screw group. Mean ± SD radiological union time in DHS with de-rotation screw group was 12.5 ± 1.225 weeks and in cannulated hip screw group was 13.61 ± 1.559 weeks. Conclusion: The functional outcome of fixation by DHS with de-rotation screw was better than fixation by cannulated hip screw for femoral neck fracture in adults. JCMCTA 2022 ; 33 (1) : 112-117